2017
DOI: 10.3390/su9122383
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bioeconomy Sectors and Natural Resources in EU Economies: A Social Accounting Matrix-Based Analysis Approach

Abstract: Abstract:The bio-based economy will be crucial in achieving a sustainable development, covering all ranges of natural resources. In this sense, it is very relevant to analyze the economic links between the bioeconomic sectors and the rest of the economy, determining their total and decomposed impact on economic growth. One of the major problems in carrying out this analysis is the lack of information and complete databases that allow analysis of the bioeconomy and its effects on other economic activities. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Building on the seminal work of Müller et al [11], Mainar and Philippidis [3] update to the year 2010 and further augment the biobased sector accounts to encompass additional sources of biomass, as well as contemporary applications of biomass in the fields of liquid fuels, electricity and chemicals. The resulting BioSAMs have been subsequently employed by Fuentes-Saguar et al [14] to calculate output and employment multipliers for biobased activities in the 28 EU MS. Simply employing mean multiplier values, the authors compare with the EU bloc average.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Building on the seminal work of Müller et al [11], Mainar and Philippidis [3] update to the year 2010 and further augment the biobased sector accounts to encompass additional sources of biomass, as well as contemporary applications of biomass in the fields of liquid fuels, electricity and chemicals. The resulting BioSAMs have been subsequently employed by Fuentes-Saguar et al [14] to calculate output and employment multipliers for biobased activities in the 28 EU MS. Simply employing mean multiplier values, the authors compare with the EU bloc average.…”
Section: Introductionmentioning
confidence: 99%
“…This study also employs the BioSAMs to undertake a structural analysis of the EU MS biobased sectors, although it improves on the study by Fuentes-Saguar et al [14] in two ways. Firstly, following other relevant studies [12,13], the current study calculates both backward-linkage (BL) and forward-linkage (FL) multipliers (see Section 2 and Supplementary Materials), which in comparison with Fuentes-Saguar et al [14], yields a more comprehensive picture of the structural influence of the biobased economy. On the one hand, the sum of the total BL multiplier effect from a given sector 'j' is equivalent to the output multiplier, as both represent the cumulative value of economic activity resulting from an additional unit of final demand for a given commodity [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the short-run relationship cannot be confirmed in two out of the three models. One possible reason for this finding is that the concept of bioeconomy is long-term in nature [58], and has not yet unleashed its full potential [25]. Another important reason may be that bioproducts have not fully hit commercialization [59], and consumers are generally unfamiliar with bio-based products [60].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have advocated for a study such as the one presented in this paper. For instance, Fuentes-Saguar et al [25] indicated that in the context of the growing relevance and interest in the bioeconomy across the world, research work that provides significant information on the structure of activities and their links with gross domestic product (GDP) has acquired greater importance. Also, the German Bioeconomy Council [26] stated that insights into the expectations, drivers, and barriers related to sustainable bioeconomy around the world are essential for international policy and collaboration.…”
Section: Introductionmentioning
confidence: 99%